Active methodologies for graduation in nursing: focus on the health care of older adults - Elaine Fernanda Dornelas de Souza; Amanda Gaspar Silva; Ariana Ieda Lima Ferreira da Silva
ABSTRACT Objective: To describe the experience of the use of simulation as active teaching methodology in the Developmental Psychology discipline and share its impacts on the students' learning process. Method: Based on Active Methodologies, the students in Nursing of Universidade do Oeste Paulista - Presidente Prudente-SP developed simulated visits to older users of the Family Health Strategies. Results: In accordance with the 2014 National Curriculum Guidelines and the Brazilian Unified Health System, particularities of the needs of older adults at their homes were problematized. Final considerations: Addressing the biopsychosocial needs and integrality associated with the health of older adults in simulated home visits provides a differentiated instrument in the development of skills and competence of future nurses.